2008
DOI: 10.1007/s00530-008-0117-1
|View full text |Cite
|
Sign up to set email alerts
|

An efficient ad recommendation system for TV programs

Abstract: With broadcast Television (TV) going digital, the number of channels and the programs aired have increased tremendously. Millions of audiences of various categories such as adults, children, youth and families watch these programs. Advertisements (ads) aired during these programs are targeted to reach these varied audiences and are the main revenue earners for TV broadcasters. While TV broadcasters have the task of scheduling hundreds of ads during the various ad breaks of programs, it is important that the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…As an example of this Negroponte (1995) suggested the concept of a personal newspaper: "the daily me". Subsequently, media personalisation technologies have caught the attention of both commercial media and public service media, as well as among many ICT engineers and programmers (e.g., Chesnais, Mucklo, & Sheena, 1995;Ali & van Stam, 2004;Velusamy et al, 2008;Ricci et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As an example of this Negroponte (1995) suggested the concept of a personal newspaper: "the daily me". Subsequently, media personalisation technologies have caught the attention of both commercial media and public service media, as well as among many ICT engineers and programmers (e.g., Chesnais, Mucklo, & Sheena, 1995;Ali & van Stam, 2004;Velusamy et al, 2008;Ricci et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…They found that the recommendation system could not only help users find the right products, but also to find the right products at the right time. In addition to digital libraries and electronic business, recommendation systems can also be applied to other applications, such as movies (Lekakos & Caravelas, 2008), academic papers (Middleton, Shadbolt, & De Roure, 2004), and TV (Velusamy, Gopal, Bhatnagar, & Varadarajan, 2008). Likewise, we can also use recommendation systems to support learning, where, in turn, learning objects can easily and efficiently be accessed and learners can be guided to interesting or useful learning objects (Burke, 2002).…”
Section: Related Work 21 Video Summarization and Recommendationmentioning
confidence: 97%
“…Smart TV is the most liked medium for watching the news, videos, games, music, etc., [54]. It can stream every available type of web content without time or location constraints.…”
Section: Watching Behavior On Smart Tvmentioning
confidence: 99%